The Effectiveness Using Management Tools To Develop Public Relations Of Medical And Public Health Secretary Of College Of Allied Health Sciences, Suan Sunandha Rajabhat University (Journal of Namibian Studies : History Politics Culture, 2023)
The efficiency which management methods can be used to improve public relations of Medical and Public Health Secretary, College of Allied Health Sciences Suan Sunandha Rajabhat University. It's called action research. The objectives were as follows: 1) to examine the level of effectiveness of utilizing the PDCA quality management cycle in organizational public relations; 2)Examine media formats, media production, page access evaluation, and the growth of digital media in public relations; 3) To investigate the efficacy of management tools for public relations development and 4) Examine the influence of PDCA cycle-based quality management on corporate public relations in the digital age. The sample group consisted of 400 students who followed the Medical and Public Health Secretary Department's page and completed a questionnaire to gauge their views on the quality management cycle (Plan: Do: Check: Act) or PDCA principles in management for development work. So, to do the analysis of data employs frequency, the percentage of statistical inference was utilized by the Chi-Square Test and Multiple Linear Regression. The efficacy of using management tools to develop public relations work is determined by analyzing media formats that reach target groups. The result indicated that the level with the highest mean is action (Do), followed by review (Check) and enhancement (Act), and the level with the lowest mean is planning (Plan). Examining media formats and media production revealed that Action for digital media development for public relations received the highest score (4.83). Next, the effectiveness of using management tools to improve public relations is in the highest level and the influence of PDCA cycle-based quality management on corporate public relations in the digital age and the effectiveness of using the PDCA quality management cycle in public relations in the digital age yielded a P-value 0.05 and an R2 value of 0.95, indicating a 90% statistically significant impact on public relations development management.